Surface shapes and surrounding environment analysis of single‐ and double‐stranded DNA‐binding proteins in protein‐DNA interface. Issue 7 (16th April 2016) - Wang, Wei; Liu, Juan; Sun, Lin
ABSTRACT: Protein‐DNA bindings are critical to many biological processes. However, the structural mechanisms underlying these interactions are not fully understood. Here, we analyzed the residues shape (peak, flat, or valley) and the surrounding environment of double‐stranded DNA‐binding proteins (DSBs) and single‐stranded DNA‐binding proteins (SSBs) in protein‐DNA interfaces. In the results, we found that the interface shapes, hydrogen bonds, and the surrounding environment present significant differences between the two kinds of proteins. Built on the investigation results, we constructed a random forest (RF) classifier to distinguish DSBs and SSBs with satisfying performance. In conclusion, we present a novel methodology to characterize protein interfaces, which will deepen our understanding of the specificity of proteins binding to ssDNA (single‐stranded DNA) or dsDNA (double‐stranded DNA). Proteins 2016; 84:979–989. © 2016 Wiley Periodicals, Inc.